2013
DOI: 10.1165/rcmb.2013-0049oc
|View full text |Cite
|
Sign up to set email alerts
|

Human Tracheobronchial Basal Cells. Normal versus Remodeling/Repairing PhenotypesIn VivoandIn Vitro

Abstract: Human tracheobronchial epithelial (TBE) basal cells (BCs) function as progenitors in normal tissue. However, mechanistic studies are typically performed in vitro and frequently use BCs recovered from patients who die of nonrespiratory disease. It is not knownwhether the cadaveric epithelium (1) is undergoing homeostatic remodeling and/or repair, or (2) yields BC clones that represent homeostatic processes identifiedin tissue. We sought to compare the phenotype of TBE-BCs with that of BCs cultured under optimal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 32 publications
(47 reference statements)
1
50
0
Order By: Relevance
“…Our data are the first to show enhanced TF expression under allergic inflammatory conditions in mice, indicating that this model will be useful for studying the function of TF in asthma. The distribution of TF in mouse lung epithelial cells was unknown, although, in humans, it is considered a basal cell marker (47,48). We show that, as in humans, TF is abundantly expressed in basal epithelial cells in the mouse airway.…”
Section: Discussionmentioning
confidence: 69%
“…Our data are the first to show enhanced TF expression under allergic inflammatory conditions in mice, indicating that this model will be useful for studying the function of TF in asthma. The distribution of TF in mouse lung epithelial cells was unknown, although, in humans, it is considered a basal cell marker (47,48). We show that, as in humans, TF is abundantly expressed in basal epithelial cells in the mouse airway.…”
Section: Discussionmentioning
confidence: 69%
“…Lineage tracing and other studies have shown that in the adult mouse lung there is only very slow turnover of the mucociliary epithelium and replacement of luminal cells from basal cells and their immediate progeny (Ghosh et al, 2013(Ghosh et al, , 2011Hong et al, 2004;Rock et al, , 2009Watson et al, 2015). However, following cell damage by agents typically used experimentally -for example naphthalene, which kills secretory Club cells, or SO 2 gas, which kills all luminal cells -or viral infection there are rapid changes in the behavior and proliferation of the basal cells so that they quickly regenerate the epithelium and restore barrier function.…”
Section: Basal Progenitor Cellsmentioning
confidence: 99%
“…The number of progenitor cells was determined using the limiting dilution assay (23) modified for lung (24)(25)(26).…”
Section: Clone-forming Cell Frequencymentioning
confidence: 99%
“…Cell surface phenotype was determined using antibodies and sorting methods as previously described (24,27). Cell cycle analysis was performed using the method of Krishan (28) and assayed on a Gallios 561 instrument equipped with a Hypercyte 96-well plate reader (Beckman Coulter, Indianapolis, IN).…”
Section: Flow Cytometrymentioning
confidence: 99%
See 1 more Smart Citation